Preparation and characterization of PVC-Al2O3- LiClO4 composite polymeric electrolyte - Ahmad A.; Rahman M.Y.A.; Mohd Noor S.A.; Bakar M.R.A. (2023)
Ionic conductivity of composite polymer electrolyte PVC-Al 2O3-LiClO4 as a function of Al 2O3 concentration has been studied. The electrolyte samples were prepared by solution casting technique. Their ionic conductivity was measured using impedance spectroscopy technique. It was observed that the conductivity of the electrolyte varies with Al2O3 concentration. The highest room temperature conductivity of the electrolyte of 3.43 10-10 S.cm-1 was obtain at 25% by weight of Al2O3 and that without Al2O3 filler was found to be 2.43 10-11 S.cm-1. The glass transition temperature decreases with the increase of Al2O 3 percentage due to the increasing amorphous state, meanwhile the degradation temperature increases with the increase of Al2O 3 percentage. Both of these thermal properties influence the enhancement of the conductivity value. The morphology of the samples shows the even distribution of the Al2O3 filler in the samples. However, the filler starts to agglomerate in the sample when high percentage of Al2O3 is being used. In conclusion, the addition of Al2O3 filler improves the ionic conductivity of PVC-Al2O3LiClO4 solid polymer electrolyte.